PELATIHAN PEMBUATAN VCO FERMENTASI DAN SABUN VCO DENGAN FORTIFIKASI EKSTRAK BUAH NAGA DI KELURAHAN SABILA KECAMATAN MALLAWA KABUPATEN MAROS - Nur Haedar; Permatasari, Nur Umriani; Dwayana, Zaraswati; Johanes, Eva; Umar, Ruslan; Gani, Fuad; Muhammad, Syafrian Nur; Zhafirah, Nur Afifah (JURNAL PENGABDIAN PAPUA, 2024)
Fermented Virgin Coconut Oil (VCO) is a processed oil where the manufacturing process uses baker's yeast, is easy to make and has simple equipment. The high content of lauric acid and vitamin E is beneficial for skin health, so it is often used as a raw material for making soap. One way to improve the function of VCO is the fortification process with dragon fruit which contains high antioxidants. This activity aims to increase community entrepreneurial interest by utilizing local potential into health and beauty products so that it can improve the family economy. Coconut and dragon fruit are the main raw materials for VCO and VCO soap which are easy to find in Sabila Village, Mallawa District, Maros Regency. Community service activities (PKM) begin with counseling/lectures on sterilization techniques, packaging methods and online product marketing. Followed by training on how to make VCO by fermentation and VCO soap with fortified dragon fruit extract. The results of the activity showed the enthusiasm of the participants during the discussion and the results of the pre- and post-test evaluation showed an increase in participants' knowledge about VCO and VCO soap by 78.0% after the training.